Introduction to "Immunotherapies for Multiple Myeloma" - Massimo Offidani; Maria Teresa Petrucci (MDPI AG, 2020)
Multiple myeloma (MM) is the second most common hematological cancer after diffuse large B-cell lymphoma, accounting for about 10% of all blood cancers [...]